2016
DOI: 10.1186/s40658-016-0139-2
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated calculation of image-derived input function in simultaneous PET/MRI in a sheep model

Abstract: BackgroundObtaining the arterial input function (AIF) from image data in dynamic positron emission tomography (PET) examinations is a non-invasive alternative to arterial blood sampling. In simultaneous PET/magnetic resonance imaging (PET/MRI), high-resolution MRI angiographies can be used to define major arteries for correction of partial-volume effects (PVE) and point spread function (PSF) response in the PET data. The present study describes a fully automated method to obtain the image-derived input functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…However in PET studies of the brain, calculation of the IDIF is challenged by two factors: PVE [231,232] due to the small size of the blood pools, and subject motion [232,233]. Various approaches have been proposed to extract an accurate IDIF that can be classified into PET-only based methods [232,[234][235][236][237][238][239][240][241][242][243][244], stand-alone PET and MR-based methods [228,245,246], and fully-integrated PET/MR-based methods [247][248][249]. Combined PET/MR can potentially allow researchers to address the aforementioned challenges (PVE and subject motion) in an automatic way [228,248,249], in addition to bearing a logistic advantage.…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…However in PET studies of the brain, calculation of the IDIF is challenged by two factors: PVE [231,232] due to the small size of the blood pools, and subject motion [232,233]. Various approaches have been proposed to extract an accurate IDIF that can be classified into PET-only based methods [232,[234][235][236][237][238][239][240][241][242][243][244], stand-alone PET and MR-based methods [228,245,246], and fully-integrated PET/MR-based methods [247][248][249]. Combined PET/MR can potentially allow researchers to address the aforementioned challenges (PVE and subject motion) in an automatic way [228,248,249], in addition to bearing a logistic advantage.…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…However, the single-target correction PVC is highly dependent on both the accurate alignment of PET and MRI data and the exact estimation of the PSF of the PET system. In addition to being highly sensitive to motion artifacts, both of these methods inherently assume that the tracer concentration distribution (and the resulting parcellation) varies spatially, but not temporally (4)(5)(6)(7)(8)(9)(10)(11)(12). However, the importance of considering the temporal variability of the target and background regions during IDIF extraction was emphasized previously (29).…”
Section: Discussionmentioning
confidence: 99%
“…To obviate the need for the arterial input function (AIF) in brain studies, several methodologies have been proposed to extract an image-derived input function (IDIF) directly from PET images (4)(5)(6)(7)(8)(9)(10)(11)(12). These studies demonstrated that the extraction of an IDIF from a dynamic PET dataset requires 3 main tasks: the accurate definition of a blood-pool region, the accurate correction for subject motion, and the exact correction of extracted time-activity curves for partial-volume effects because of the small diameter of the internal carotid arteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MRI data could be used to assist and complement PET data in several ways [188]. Using TOF MR angiography can improve the delineation of the arterial volume in PET [184,[189][190][191]. The IDIF could be implemented in an automated pipeline to provide absolute values of cerebral glucose metabolism in a clinically feasible manner [192].…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%